First Clinical Experience with Anti-myelin Oligodendrocyte Glycoprotein Antibody-Positive Optic Neuritis - Heckmann, Jan; Todorova, Margarita; Müller, Stefanie; Broser, Philip Julian; Sturm, Veit (Klinische Monatsblätter für Augenheilkunde, 2020)
Background Antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) have been consistently found in a range of demyelinating disorders. In this context, MOG-IgG-associated optic neuritis (ON) has been suggested as a new subset of optic neuropathy. However, clinical manifestations and distinctive characteristics have only rarely been described.Patients and Methods A retrospective case series of three patients with MOG-IgG-associated ON. Clinical morphological features using imaging techniques are presented.Results Three patients (8-year-old boy, 28-year-old female, 48-year-old male) were included. An 8-year-old boy suffered from a bilateral ON with severe visual loss. The best-corrected visual acuity (BCVA) was 0.05 in the right eye and finger counting in the left eye. The patient had a previous episode of acute disseminated encephalomyelitis (ADEM) with a right abducens nerve palsy. Visual acuity recovered after repeated cycles of intravenous methylprednisolone pulse therapy and 10 cycles of plasma exchange. During the last follow-up, BCVA was 0.9 in the right eye and 0.8 in the left eye. A 28-year-old female presented with a bilateral ON. Her BCVA was 0.5 in the right eye and 0.8 in the left eye. She fully recovered with pulse methylprednisolone therapy (1000 mg/d) with tapering after the second cycle and had a BCVA of 1.0 during the last follow-up visit. A 48-year-old male suffered from a relapsing bilateral ON. At first presentation, BCVA was 0.1 in the right eye and finger counting in the left eye. BCVA fully recovered after each pulse therapy with intravenous methylprednisolone (two cycles). Since the first relapse, the patient has been receiving long-term immunosuppression with rituximab. Despite rituximab and low-dose oral prednisone, the patient had another relapse with a left ON. After a third cycle with intravenous methylprednisolone, he partially recovered. BCVA at last follow-up was 1.0 in the right and 0.8 in the left eye.Conclusions MOG-IgG antibodies have been identified in different acquired demyelinating syndromes. The patients reported had an ADEM followed by bilateral ON, an isolated bilateral ON, and a relapsing bilateral ON. Individual treatment strategies led to substantial visual recovery in all patients. We recommend inclusion of MOG-IgG antibodies in the diagnostic workup at least after the first recurrence of ON since they can serve as a diagnostic and potential prognostic tool and might lead to specific therapeutic recommendations.
Keywords: myelin oligodendrocyte glycoprotein; optic neuropathy; visual loss; demyelinating diseases